Digital technology-enhanced reconstruction and rehabilitation following mandible fibular flap grafting with implants: a case report - Li, Shuang; Liu, Jian; Li, Jian; Yin, Baoheng; Feng, Yuanyong; Liu, Yanshan; Bai, Na (Frontiers in Dental Medicine, 2025)
ObjectiveIn this paper, we report a case of missing posterior teeth after mandibular fibular flap grafting and implant restoration by means of a digital restorative process, in the hope that the application of digital technology will help the patient to comfortably establish an adapted occlusal relationship.Case reportA 29-year-old male patient developed a left mandibular ameloblastoma measuring 35 mm × 35 mm × 25 mm, which did not invade the surrounding bone tissue, submandibular gland tissue, or lymph nodes. After resection of an 85 mm mandibular segment, the patient was reconstructed using a gastrocnemius flap transfer. He was then referred to our institution for postoperative dental implant restoration. The restorative process incorporated various digital technologies including a digital facebow, intraoral scanner, extraoral scanner, facial scanner, and CAD/CAM systems. Following 1 year post-implantation, the patient received second-stage implantation alongside autologous dermal allograft (ADM) transplantation; subsequently, a temporary prosthesis was fabricated while employing an electronic articulator to accurately transfer occlusal relationships before finalizing with permanent restorations. The integration of digital technology throughout this restorative process enhanced both precision and comfort.ConclusionsThis case study offers an innovative and efficient clinical approach for addressing dentition defect following mandibular reconstruction via advanced digital methodologies.